2019
DOI: 10.1182/blood.2019002038
|View full text |Cite
|
Sign up to set email alerts
|

Rapid progression of adult T-cell leukemia/lymphoma as tumor-infiltrating Tregs after PD-1 blockade

Abstract: The investigators present their analysis of primary cells from patients with human T-cell leukemia virus 1–associated adult T-cell leukemia/lymphoma treated in a phase 2 clinical trial with nivolumab to elucidate mechanisms of hyperprogression that halted the trial after just 3 patients received a single treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 43 publications
(54 reference statements)
1
57
0
1
Order By: Relevance
“…One speculates that infected cells differentiate into various hematopoietic cells including T cells, B cells, monocytes, and neutrophils. HTLV-1 infection to immature cells was also suggested by the report that ATL clones with the identical integration site of the provirus and different T-cell receptor gene rearrangement were found in the same patients [64]. It is possible that viral gene(s) modulate the differentiation of infected cells.…”
Section: How Hbz Modulates Infected Cellsmentioning
confidence: 91%
“…One speculates that infected cells differentiate into various hematopoietic cells including T cells, B cells, monocytes, and neutrophils. HTLV-1 infection to immature cells was also suggested by the report that ATL clones with the identical integration site of the provirus and different T-cell receptor gene rearrangement were found in the same patients [64]. It is possible that viral gene(s) modulate the differentiation of infected cells.…”
Section: How Hbz Modulates Infected Cellsmentioning
confidence: 91%
“…The molecular mechanism behind this phenomenon remains unknown, but authors detected an increase in cells expressing proliferation marker Ki67 and a decrease in apoptosis marker Caspase-3 [71]. In certain cancers, acute T-cell lymphocytic leukaemia as a prime example, PD-1 is proposed to function as a tumour suppressor [55]. The rapid growth of PD-1 expressing cancer cells after blocking PD-1 suggests its inhibitory role so widely observed in T-cells [73].…”
Section: Pd-1 Intrinsic Signallingmentioning
confidence: 99%
“…As for the other immunotherapy, immune checkpoint inhibitors such as programmed cell death-1 (PD-1) inhibitors and programmed cell death-ligand 1 (PD-L1) inhibitors are also expected to show high efficacy for patients with ATL. However, it has been reported that patients with indolent ATL progress rapidly after receiving PD-1 inhibitor (nivolumab) therapy [49,50]. In a small Japanese study of patients with aggressive ATL, no patient showed characteristics similar to those in the cases reported by Ratner et al [49][50][51].…”
Section: Remaining Issuesmentioning
confidence: 99%
“…However, it has been reported that patients with indolent ATL progress rapidly after receiving PD-1 inhibitor (nivolumab) therapy [49,50]. In a small Japanese study of patients with aggressive ATL, no patient showed characteristics similar to those in the cases reported by Ratner et al [49][50][51]. An anti-tumor role of the PD-1/PD-L1 pathway might be different between the indolent and aggressive stages of ATL.…”
Section: Remaining Issuesmentioning
confidence: 99%